Implant-retained craniofacial prostheses for facial defects - Federspil, Philipp A. (German Medical Science GMS Publishing House, 2011)
Craniofacial prostheses, also known as epistheses, are artificial substitutes for facial defects. The breakthrough for rehabilitation of facial defects with implant-retained prostheses came with the development of the modern silicones and bone anchorage. Following the discovery of the osseointegration of titanium in the 1950s, dental implants have been made of titanium in the 1960s. In 1977, the first extraoral titanium implant was inserted in a patient. Later, various solitary extraoral implant systems were developed. Grouped implant systems have also been developed which may be placed more reliably in areas with low bone presentation, as in the nasal and orbital region, or the ideally pneumatised mastoid process. Today, even large facial prostheses may be securely retained. The classical atraumatic surgical technique has remained an unchanged prerequisite for successful implantation of any system. This review outlines the basic principles of osseointegration as well as the main features of extraoral implantology.